Hegel’s Excess - Ugilt, Rasmus (Stasis, 2016)
In this article I present a reading of the transition from the first to the second books of Hegel’s Logic, focusing on the Encyclopedia Logic. In particular I investigate the notion of the excess (das Maßlose), which is the final concept Hegel discusses in the first book of that version of the Logic. I set the stage for this interpretation by briefly introducing the work of two other Hegel scholars: Dieter Henrich and Slavoj Žižek. Each of them presents a reading of the same transition I am focusing on and argue, as I do, that we can find the key to Hegel’s Logic in it. Henrich focuses on autonomous negation, Žižek on retroactivity. My aim in the article is to manouvre between the suggestions of Henrich and Žižek and to provide a new approach to understanding Hegel in doing so.